Downright Different. On Oskar Szwabowski’s Book "Nekrofilna produkcja akademicka i pieśni partyzantów" (Necrofiliac Academic Production and the Songs of Partisans) - Kruszelnicki, Michał; Kruszelnicki, Wojciech (Hybris, 2020)
The article comments the stronger and the more disputable points of Oskar Szwabowski’s book Necrofiliac Academic Production and the Songs of Partisans (2019). The authors engage in a polemics with the assertion that autoethnography is able to depict more efficiently than other scientific discourses the reality of the university after the neo-liberal reforms. We also oppose „the workers’ perspective” as promoted by O. Szwabowski, which is to replace the traditional view of the university as an elitist site and of the faculty as a particularly privileged class. Further, the article points out at certain shortcomings of theoretical Marxism which O. Szwabowski uses to criticize and envision the change of the functioning of the academic milieu along with the transformation of the very way we perceive social research – from an individualistic and competetive perspective, to one that is collective and geared in social engagement and intervention. Ultimately, we charge Oskar Szwabowski with an inconsistency which amounts to a contradiction between his notorious call upon academics to realize that the university has become a mass-production company, and the faculty have been turned into the new proletariat, and his resonant grievance upon the poor conditions of work therein.